ANALISIS PERSEPSI GEN Z TERHADAP PHISING - Peter Aditya Prabaswara,; Dewi Kartika Sari,; Amir Machmud NS, (Journal of Innovation Research and Knowledge, 2025)
The development of digital media has facilitated communication while simultaneously increasing the risk of cybercrimes such as phishing and hoaxes, particularly among Generation Z (Gen Z). Despite having broad access to information, Gen Z still faces challenges in detecting and anticipating digital threats due to low cybersecurity literacy. The purpose of this study is to analyze Generation Z’s perceptions of phishing threats within the context of digital communication and to identify how they utilize verbal descriptions, proxemic cues, and artifactual elements to recognize and respond to suspicious digital information. This research employs a qualitative approach using narrative study methods and data triangulation through interviews and observations with 15 Gen Z participants. The results indicate that although most informants have not been direct victims of phishing, they demonstrate early awareness in recognizing anomalies in digital messages through verbal, proxemic, and artifactual approaches. The findings show that Gen Z intuitively assesses the validity of information based on the social distance of the source (proxemics) and visual elements such as media logos, professional design, and credible sources (artifacts).